The effects of BaTiO3 on the handleability and mechanical strength of the prepared piezoelectric calcium phosphate silicate for bone tissue engineering. Issue 12 (15th June 2023) - Wu, Tao; Ji, Xiujuan; Zhang, Zaishan; Wang, Shun; Zhou, Jingqiu; Meng, Lisha; Liu, Xinyu; Yu, Hailong; Gong, Tianxing; Liu, Yao
Abstract: Natural bone is a piezoelectric material that can generate electrical signals when subjected to an external force. Although many studies have attempted to develop piezoelectric biomaterials for bone regeneration, post-treatment steps, such as sintering, are always needed. In this study, we prepared an injectable and piezoelectric bone substitute based on nanosized BaTiO3 (nBT)-added calcium phosphate silicate (CPS). The impacts of nBT on the CPS handleability and mechanical strength were characterized, and show that adding nBT could improve the CPS handleability but affect the CPS mechanical strength in a concentration-dependent manner (from 25.3 ± 1.0 MPa for 10BC to 13.5 ± 1.0 MPa for 40BC). In addition, our approach could fabricate a piezoelectric bone substitute with comparable piezoelectricity to the native bone without any post-treatment. The in vitro analyses demonstrated that nBT/CPS was biocompatible and could promote osteoblast differentiation. In conclusion, our results strongly indicate that the injectable formulation based on nBT/CPS can be a promising candidate in bone tissue engineering, and further research is needed to investigate the biomaterial's performance in bone defect animal models. Graphical abstract: Image 1